Development of a prototype mechanically moveable and height-adjustable ladder / Muhammad Aiman Mat Nawi - Mat Nawi, Muhammad Aiman (2023)
This project is presenting an implement of mechanically moveable and height adjustable ladder (MeMoHAL). By using MeMoHAL the cost of purchasing ladder can be save as it consists of two features on one particular product which preventing loss of money to purchase two different ladders with different feature. This project discusses about the ladder, the advantages of the MeMoHAL , the product implementation and results that obtained from the product. In conclusion based on the designed MeMoHAL, authors discussed the advantages and points need to be considered when working on the product.